(untitled) (Bangladesh Veterinarian, 2022)
An assessment of goat diseases was done in 1808 goats in one farm in Dhaka, Bangladesh. Abortion (1.7%), abscess (1.1%), actinomycosis (1.1%), bloat (2.1%), conjunctivitis (2.6%), diarrhoea (31.1%), dystocia (0.3%), contagious ecthyma (4.4%), fever (2.7%), fox bite (1.1%), lameness (9.0%), malnutrition (3.2%), mange (6.2%), mastitis (1.7%), mechanical (1.2%), pneumonia (27.4%), poisoning (0.8%), retention of placenta (0.6%), tympany 1.5% and urolithiasis (0.4%) were diagnosed. The Bangladesh Veterinarian (2020) 37(1 - 2): 14-20